Major Thromboembolic Complications in Liver Transplantation: The Role of Rotational Thromboelastometry and Cryoprecipitate Transfusion. Issue 8 (August 2021) - Nguyen-Buckley, Christine; Gao, Wei; Agopian, Vatche; Wray, Christopher; Steadman, Randolph H.; Xia, Victor W.
Abstract : Background: Although hemorrhage is a major concern during liver transplantation (LT), the risk for thromboembolism is well recognized. Implementation of rotational thromboelastometry (ROTEM) has been associated with the increased use of cryoprecipitate; however, the role of ROTEM-guided transfusion strategy and cryoprecipitate administration in the development of major thromboembolic complications (MTCs) has never been documented. Methods: We conducted a study on patients undergoing LT before and after the implementation of ROTEM. We defined MTC as intracardiac thrombus, pulmonary embolism, hepatic artery thrombosis, and ischemic stroke in 30 d after LT. We used a propensity score to match patients during the 2 study periods. Results: Among 2330 patients, 119 (4.9%) developed MTC. The implementation of ROTEM was significantly associated with an increase in cryoprecipitate use (1.1 ± 1.1 versus 2.9 ± 2.3 units, P < 0.001) and MTC (4.2% versus 9.5%, P < 0.001). Further analysis demonstrated that the use of cryoprecipitate was an independent risk factor for MTC (odds ratio 1.1, 95% confidence interval 1.04-1.24, P = 0.003). Patients with MTC had significantly lower 1-y survival. Conclusions: Our study suggests that the implementation of ROTEM and the use of cryoprecipitate play significant roles in the development of MTC in LT. The benefits and risks of cryoprecipitate transfusion should be carefully evaluated before administration. Abstract : Supplemental Digital Content is available in the text.